Isolation and structure of the fibril protein, a major component of the internal ribbon for Spiroplasma swimming - Sasajima, Yuya; Kato, Takayuki; Miyata, Tomoko; Kawamoto, Akihiro; Namba, Keiichi; Miyata, Makoto (Frontiers in Microbiology, 2022)
Spiroplasma, which are known pathogens and commensals of arthropods and plants, are helical-shaped bacteria that lack a peptidoglycan layer. Spiroplasma swim by alternating between left- and right-handed helicity. Of note, this system is not related to flagellar motility, which is widespread in bacteria. A helical ribbon running along the inner side of the helical cell should be responsible for cell helicity and comprises the bacterial actin homolog, MreB, and a protein specific to Spiroplasma, fibril. Here, we isolated the ribbon and its major component, fibril filament, for electron microscopy (EM) analysis. Single-particle analysis of the fibril filaments using the negative-staining EM revealed a three-dimensional chain structure composed of rings with a size of 11 nm wide and 6 nm long, connected by a backbone cylinder with an 8.7 nm interval with a twist along the filament axis. This structure was verified through EM tomography of quick-freeze deep-etch replica sample, with a focus on its handedness. The handedness and pitch of the helix for the isolated ribbon and fibril filament agreed with those of the cell in the resting state. Structures corresponding to the alternative state were not identified. These results suggest that the helical cell structure is supported by fibril filaments; however, the helical switch is caused by the force generated by the MreB proteins. The isolation and structural outline of the fibril filaments provide crucial information for an in-depth clarification of the unique swimming mechanism of Spiroplasma.